Проблеми збереження середмістя історичного міста України - Рибчинський, О. В.; Rybchynskyi, O. (Видавництво Львівської політехніки, 2019)
У статті з’ясовано, що значення середмістя у формуванні історичного міста України є недооцінене. В результаті аналізу існуючої структури поселення та збереженості історичної забудови визначено, що середмістя потребують збереження культурної самобутності, архітектурної спадщини, локальних цінностей, традицій та ідентичності історичного міста.

The article clarifies meaning of downtown in the process of forming the historical towns of Ukraine is underestimated. As a result of analysis of the existing settlement structure and the preservation of historical development, it has been determined that the towns need to preserve cultural identity, architectural heritage, local values, traditions and identity of the historic city. Urban building value in the meanwhile is determined by the planning scheme, the importance of the area for the city, the picturesqueity that is revealed in the general panorama of the city. Planning scheme is reflected in the compositional typology of the city center - the system of location of the main buildings of the city, as well as the quality of residential development. The architectural and aesthetic value of the development of the city center is shaped by several factors: the stages of construction, the representation of architectural styles, values for world and Ukrainian architecture, and some architectural and artistic elements. Emotional and artistic value lies in the fact that the city as a complex and key-center was formed proportionally and organically to the way of perception and knowledge of the environment of the whole city. The colors, decorations of the facades and interiors show such architectural decisions with the "patina of time", they regulate and influence the psychological state of a person in a historically formed urban environment. The scientific value of architecture in the city centers of the prevailing nature and features of building layers, sequences and ways of changing the image of houses. Layers show that as a result of alterations and completions in buildings preserved various structures, walls, details that indicate the historical system of creating architecture. The sequence and ways of changing the image of the buildings show architectural and aesthetic decisions made at different times, which are proofs of historical evolution. Therefore, the city center is a reflection of the historical, cultural and spatial identity of the city. Scenery is an important aspect of the perception of the city, the images of which began to attract artists in the nineteenth century. Through the perception of the picturesqueness of the centers of historical cities, the space with open and unambiguous forms, expressive architectural images, harmonious coloring, diverse texture and texture of surfaces filled with actions (fairs, festivals, religious holidays, political actions, daily), harmonious panoramas of settlements is revealed in a new way. , attractive for artistic fixation (literature, painting, graphics, photography). Analysis of urban landscapes with distinct ethnic details and objects, forms and symbols makes it possible to consider pictoriality as a certain metaphor, based on which each time a unique combination of the natural landscape and traditional architectural and spatial layout. According to the previous characteristics, according to the author, in the register of monuments of urban development it is worth mentioning in the city of Lviv, Gorodok, Sambir, Drohobych, Dobromyl, Stryi, Zhovkva, Ivano-Frankivsk, Kolomyia, Bratslav, Shargorod, Rogatyn, Skala Podilska, Nova Ushitsa, Kamyanka Buska, Gaisyn, Buchach, Berdychiv. Due to the systematization of historical information, it is possible to predict the peculiarities of exhibiting material and intangible cultural heritage in the city. Thus, intangible values are very important for the meanwhile because they represent unique urban traditions, customs, ordinances, celebrations, honoring celebrities and places of memory. Based on te of preservation, they should be considered objects of cultural heritage. In view of the historical volumetric spatial and compositional-planning features, modernization and regulatory processes in the city area remain the source of architectural and urban-based theoretical studies. Therefore, in the center of the city, it is necessary to open and protect authentic material and intangible monuments, as well as systematically think about their modern use. It has been discovered that the city has past, preserved in individual and collective memory, preserves old relics and architectural objects, objects of applied art, science and technology, works of art, characterized by sentimentality and romanticism.
Downtovn preservation problems of the historical towns of Ukraine
Keywords: середмістя; система цінності; культурна спадщина; пам’ятки містобудування; downtown; system of value; cultural heritage; monuments of city planning; 719; 711.27